Rowan Williams's Shari'a Lecture: Law, Love, and the Legacy of the Enlightenment - Depoortere, Frederiek (Political theology, 2012)
In 2008, Rowan Williams sparked a huge controversy in Britain by pleading for more recognition of shari'a law. The present paper aims to explore Mike Higton's suggestion that this plea actually results from Williams's defence of the Enlightenment. The paper will first show that Williams's plea for increased recognition of shari'a is in line with the Enlightenment ideal of sociability. It will subsequently show that this does not mean that Williams gives up on the importance of the secular law. Special attention will be given to the two fundamental principles behind Williams's views on shari'a and these principles will be developed with the help of Edward Schillebeeckx's view of ‘the humanum’. Finally, the paper will also indicate that Williams's two fundamental principles offer a way to better understand the biblical commandment to love one's neighbour—a view that will be developed with reference to the work of Slavoj Zizek.